Globalization : a very short introduction - Steger, Manfred B., 1961- (Oxford : Oxford University Press, 2020)
'Globalization' is one of the defining buzzwords of our time, describing a variety of accelerating economic, political, and cultural processes that constantly change our experience of the world. This book provides an exploration of both the causes and effects of the phenomenon.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 13, 2020).
Keywords: Globalization